Microwave-assisted synthesis of pyrrolidinone derivatives using 1,1’-butylenebis(3-sulfo-3H-imidazol-1-ium) chloride in ethylene glycol - Khaligh, Nader Ghaffari; Mihankhah, Taraneh; Johan, Mohd Rafie; Titinchi, Salam J.J. (De Gruyter, 2019)
The energy efficiency of the microwave-assisted synthesis of pyrrolidinones was demonstrated using catalytic loading of 1,1'-butylene-bis(3-sulfo-3H-imidazol-1-ium) chloride as a sulfonic acid functionalized ionic liquid in ethylene glycol as green solvent. The effect of electron donating and electron withdrawing groups on aniline derivatives was studied under conventional heating and microwave irradiation. Furthermore, the cation effect of ionic liquids containing sulfonic groups on the catalytic efficiency for the synthesis of ethyl-1-phenyl-2-(4-chlorophenyl)-4-hydroxy-5-oxo-2,5-dihydro-1H-pyr-role-3-carboxylate was investigated under conventional heat. The experimental results exhibited that there is a relationship between catalytic efficiency and the number of sulfonic groups and imidazolium moieties linked by carbon spacer. © 2019 N.G. Khaligh et al., published by De Gruyter.